Assessing the association between household air pollution exposure and child heath in Mongolia: a birth-cohort study - Zaiyou Dai; Katherine E. Woolley; Emma Dickinson-Craig; Tsogzolma Bayandorj; Narangerel Gombojav; Bazarragchaa Tsogt; David Warburton; G. Neil Thomas; Semira Manaseki-Holland (Scientific Reports)
Abstract Children in Mongolia are exposed to harmful levels of household air pollution (HAP) due to a high reliance on coal for indoor cooking and heating. This study aims to assess the association between HAP and child health outcomes, in a birth cohort from Ulaanbaatar, Mongolia. A composite HAP measure was created using information on cooking and heating fuels and behaviours collected as part of a randomised control trial assessing the impact of swaddling on child health. Child health outcomes (Bayley Scales of Infant Development scores [BSID-II], pneumonia, height and weight) were collected at 7, 13, and 36 months. Linear and Cox proportional hazard model were used to assess the association between HAP and child health outcomes at each time point, adjusting for child, maternal and environmental confounding factors. An increased risk of pneumonia was observed with an increasing HAP score (adjusted hazard ratio: 1.02 [1.01, 1.04]) at 7 months). An increase in HAP exposure was associated with a decrease in the BSID mental score at 13 months (β: − 0.09 [− 0.17, − 0.01]), BSID psychomotor score at 36 months (β: − 0.12 [− 0.23, − 0.02]). A decrease in height-for-age z-score (HAZ) and weight-for-age z-score (WAZ) were associated with increased HAP exposure at 7 (HAZ β: − 0.019 [− 0.030, − 0.010] and 13 months (HAZ β: − 0.020 [− 0.030, − 0.011], and WAZ β: − 0.012 [− 0.019, − 0.005]), however only HAZ was associated with HAP at 36 months (β: − 0.011 [− 0.020, − 0.002]). An increasing HAP score was associated with an increase in the health outcome composite score at 7 months only (β: 0.019; 95% CI 0.003–0.035). HAP exposure was shown to negatively impact child health sustainably over 3 years. There are implications for development of appropriate public health policies to mitigate HAP exposure throughout Mongolia and similar Central Asia settings.